Urolithin A (UA) attenuates ferroptosis in LPS-induced acute lung injury in mice by upregulating Keap1-Nrf2/HO-1 signaling pathway - Lou, Lejing; Wang, Min; He, Jingjing; Yang, Song; Meng, Fanxi; Wang, Shijia; Jin, Xiao; Cai, Jihao; Cai, Chang (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is a life-threatening disease with high incidence and mortality rates. Urolithin A (UA) is a pomegranate intestinal flora metabolite with anti-inflammatory, antioxidant, and anti-aging properties. Ferroptosis is a critical factor in lipopolysaccharide (LPS)-induced acute lung injury (ALI). However, the link between UA and ferroptosis is unknown. The purpose of this research was to look into the role of UA in regulating LPS-induced ferroptosis in ALI. The current study used LPS to injure two models, one BEAS-2B cell injury model and one ALI mouse model. UA effectively alleviated LPS-induced ALI compared to the LPS group by lowering in vivo lung wet/dry weight ratio, reactive oxygen species, and malondialdehyde production, as well as superoxide dismutase, catalase, and glutathione depletion. Furthermore, by increasing GPX4 and SLC7A11 expression and decreasing Fe2+ levels, lung histopathological damage, inflammatory cytokine secretion, and ferroptosis levels can be significantly reduced. The Keap1-Nrf2/HO-1 pathway was upregulated by UA, which inhibited LPS-induced ALI and ferroptosis. ML385 inhibited UA’s protective effect against LPS-induced ALI. These findings suggested that UA could be a novel potential therapeutic target for ALI.